Constructing a Census of Chinese Regional Industrialization for 1933. The Case of Jiangsu and Guangdong Provinces - Xu, Yi; Tang, Zhihua (TSEG - The Low Countries Journal of Social and Economic History, 2019)
Industrialization in China over the course of the twentieth century has been spectacular. Yet, the spread of industrial development has been very uneven. In this paper, we will construct a dataset on regional manufacturing for 1933, just before the industrial take-off in the twentieth century. Given the sheer size of China, we will focus on two provinces, i.e. Jiangsu (including Shanghai) and Guangdong, both of which have been associated with a large manufacturing sector. By combining the first large scale industrial census conducted by D.K. Lieu with a large number of smaller censuses, surveys, and statistical reports, we are, for the first time, able to provide regional estimates of output value for the whole manufacturing industry by sector and region as well as for the number of modern factories and their employees.